Agrogenic – IoT Based Modern Automated Greenhouse System - Herath T.H.M.C.C.B; Dayarathne J.C; Wijekoon D.G.W.M.U.P; Dassanayake D.M.S.C; Samantha Rajapaksha; Wellalage Sasini Nuwanthika (International Journal of Engineering and Management Research, 2022)
World population growth has created a number of problems, the most serious of which is the threat of famine. In the Sri Lankan context, there is an urgent need to increase the production of crops and other crops due to the rapidly growing population of Sri Lanka. There we considered two effects. The composition of phosphorus, potassium, and nitrogen levels in the soil plays an important role. Here we have introduced a new mechanism to identify nitrogen, potassium, and phosphorous levels, which are the main factors that stimulate plant growth inside the soil. There is a required level of nitrogen, potassium, and phosphorus for a certain plant that is grown inside a greenhouse. When the line chart identifies that there is not enough nitrogen, potassium, and phosphorus in the soil, it will generate an alert through the mobile app. At the same time, arrangements have been made to supply fertilizer that contains nitrogen, potassium, and phosphorus. After the recommended life span of a plant, the productivity of the organically fertilized plant group and the group of chemically fertilized plants are compared separately. Another thing to consider is, Plant and genetic researchers have found that different wavelength factors directly contribute to plant growth. A small amount of research has been done in these areas and some research is still ongoing. Research has shown that light wavelengths affect plant growth. In this case, we have made greater use of the technical side to stimulate plant growth by controlling such wavelength factors well. Then the mobile app user can control the decoders through the mobile app and set the required amounts of light intensity. In this proposed system, Users can put the new plant species inside the greenhouse and control the light beam wavelength through the mobile app.